Economic trade-off in the optimization of carrier aggregation with enhanced multi-band scheduling in LTE-Advanced scenarios - Robalo, Daniel (2015)
This work proposes Long Term Evolution-Advanced (LTE-A) integrated Common Radio Resource Management (iCRRM) for inter-band carrier aggregation (CA) between band 7 (2.6 GHz) and band 20 (800 MHz), considering bandwidths of 5 and 20 MHz. The iCRRM entity performs component carrier (CC) scheduling and increases user’s quality of service and experience while considering mobile video traffic. The performance from a new enhanced multi-band scheduling (EMBS) algorithm is compared to the one from a basic multi-band scheduler (BMBS), an integer programming-based general multi-band scheduling (GMBS) and the case without CA. EMBS involves reduced optimization scheduling complexity and allows the allocation of UEs to one or both CCs simultaneously, whereas both BMBS and GMBS only support one CC per UE. Simulations results have shown that, for 5 MHz CCs and cell radius equal to 1,000 m, with EMBS and GMBS, the 3GPP and ITU-T’s 1% packet loss ratio (PLR) threshold is only exceeded above 58 UEs (goodputs of 7.48 and 7.40 Mbps, respectively), while with BMBS only 54 UEs (6.9 Mbps) are supported. Without CA, the minimum obtained PLR is approximately 2%. For CCs with bandwidth of 20 MHz, only EMBS has been considered. The PLR threshold is not exceeded up to 40 users and the value of QoE raises from 2.86 (for 5-MHz bandwidth) to 3.96, while a gain of 9.56 occurs in supported goodput, increasing from 7.48 to 71.53 Mbps. Results from the cost/revenue trade-off have shown substantial improvements by using CA. Although the profit increases as the price per megabyte increases, it is verified that prices can be much lower if a bandwidth of 20 MHz is available. Assuming values for the supported goodput under the PLR ≤1% range and 20 MHz CCs, it has been shown that the percentage of profit decreases at a considerably higher rate (compared to 5-MHz bandwidth), due to the lower rate of decrease from the curve for costs. Considering PLR ≤1%, the profit curve for 20 MHz CCs at 0.001 € /MByte is similar to the one for 5 MHz CCs and price of 0.01 € /MByte for the smallest cell sizes (few hundreds of meters) but starts to decrease faster for larger cells.